PERILAKU ALTRUISTIK TOKOH UTAMA DALAM NOVEL REFLEKSI SOSIAL BUDAYA SUKU TORAJA DALAM NOVEL PUYA KE PUYA KARYA FAISAL ODDANG (SOCIO-CULTURAL REFLECTION IN FAISAL ODDANG’S NOVEL PUYA KE PUYA) - Seprianus Ensen (Universitas Lambung Mangkurat, 2021)
Abstract Socio-cultural Reflection in Faisal Oddang’s Novel Puya ke Puya. This study describes the individual and socio-cultural aspects of the Toraja tribe, as reflected in the novel Puya ke Puya. This is qualitative research using the approach of the sociology of literature. This research's object is a novel entitled